2020
DOI: 10.3389/fpsyg.2020.603520
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Cueing Effect Under Rapid Presentation

Abstract: In contextual cueing, previously encountered context tends to facilitate the detection of the target embedded in it than when the target appears in a novel context. In this study, we investigated whether the contextual cueing could develop at early time when the search display was presented briefly. In four experiments, participants searched for a target T in an array of distractor Ls. The results showed that with a rather short presentation time of the search display, participants were able to learn the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…The idea that the global processing may cause the learning of task-irrelevant context under rapid presentation is also supported by a previous rapid presentation contextual cueing study (Xie et al, 2020). It revealed that the repeated local context only within a single quadrant containing the target, which was proved to be sufficient to generate contextual cueing effect with a long display presentation time (i.e., 8 s) in the study of Brady and Chun (2007), could hardly be acquired under the 300 ms rapid presentation condition (Xie et al, 2020). This suggests that global context should stay invariant to guide visual search under rapid presentation.…”
Section: Discussionmentioning
confidence: 62%
“…The idea that the global processing may cause the learning of task-irrelevant context under rapid presentation is also supported by a previous rapid presentation contextual cueing study (Xie et al, 2020). It revealed that the repeated local context only within a single quadrant containing the target, which was proved to be sufficient to generate contextual cueing effect with a long display presentation time (i.e., 8 s) in the study of Brady and Chun (2007), could hardly be acquired under the 300 ms rapid presentation condition (Xie et al, 2020). This suggests that global context should stay invariant to guide visual search under rapid presentation.…”
Section: Discussionmentioning
confidence: 62%
“…Taken together, previous studies (Chen et al, 2020(Chen et al, , 2021a) investigating visual and tactile search in multisensory arrays consisting of visual and tactile items established that contextual cues available in one-distractor-modality can be utilized in the other-target-modality. Further, redundant contexts consisting of identically positioned visual and tactile elements can enhance visual learning of the relational position of the visual target item over and above that deriving from predictive visual contexts alone.…”
Section: Crossmodal Contextual Cueing Across Visual and Tactile Modal...mentioning
confidence: 58%
“…It is important to note that, in visuotactile studies of contextual cueing, the visual and tactile stimuli need to be collocated-which necessarily limits the number of (collocated) stimuli in the display. Nevertheless, previous work from our group has consistently shown reliable cueing effects using this multi-modal set-up (Chen et al, 2020(Chen et al, , 2021b(Chen et al, , 2022a, as well as with easy, "pop-out" visual search tasks (Geyer et al, 2010;Harris and Remington, 2017). Thus, by comparing contextual facilitation of RTs in tactile search with redundant, i.e., visual and tactile, distractor contexts vs. single, i.e., tactile-only, distractor contexts, we aimed to decide between the two alternative accounts (outlined above) of crossmodal contextual cueing in search tasks.…”
Section: Goals Of the Current Studymentioning
confidence: 63%
“…This implies a need for sufficient time to process the local context around the target during visual search, before this bi-directional effect can come into play. Interestingly, Xie et al (2020) demonstrated that only repeating local context does not yield the same contextual cueing effect as repeating the entire search array when presentation time is very short. This bi-directional learning would explain why different behavioral contextual cueing studies have found that local context is still linked to the global configuration (Brady & Chun, 2007; Y.…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that only local context directly surrounding the target is learned, since repeating only such local context produced a similar effect to classical contextual cueing (Brady & Chun, 2007). However, this does not hold when presentation time is limited (Xie et al, 2020), and there has been evidence that distractor context unrelated to the target is also learned (Beesley et al, 2015a). The question thus remains whether local and/or global context is learned in contextual cueing (Goujon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%